Rapid land use change after socio-economic disturbances: The collapse of the Soviet Union versus Chernobyl - Patrick Hostert; Tobias Kuemmerle; Alexander Prishchepov; Anika Sieber; Eric F. Lambin; Volker C. Radeloff (Environmental Research Letters, 2011)
Land use change is a principal force and inherent element of global environmental change, threatening biodiversity, natural ecosystems, and their services. However, our ability to anticipate future land use change is severely limited by a lack of understanding of how major socio-economic disturbances (e.g., wars, revolutions, policy changes, and economic crises) affect land use. Here we explored to what extent socio-economic disturbances can shift land use systems onto a different trajectory, and whether this can result in less intensive land use. Our results show that the collapse of the Soviet Union in 1991 caused a major reorganization in land use systems. The effects of this socio-economic disturbance were at least as drastic as those of the nuclear disaster in the Chernobyl region in 1986. While the magnitudes of land abandonment were similar in Ukraine and Belarus in the case of the nuclear disaster (28% and 36% of previously farmed land, respectively), the rates of land abandonment after the collapse of the Soviet Union in Ukraine were twice as high as those in Belarus. This highlights that national policies and institutions play an important role in mediating effects of socio-economic disturbances. The socio-economic disturbance that we studied caused major hardship for local populations, yet also presents opportunities for conservation, as natural ecosystems are recovering on large areas of former farmland. Our results illustrate the potential of socio-economic disturbances to revert land use intensification and the important role institutions and policies play in determining land use systems' resilience against such socio-economic disturbances.
Keywords: 330; coupled human-natural systems; socio-economic disturbance; Chernobyl nuclear disaster; post-socialist land use change; transition economies; Soviet Union